Plants modify the effects of earthworms on the soil microbial community and its activity in a subtropical ecosystem. (December 2016) - Lv, Meirong; Shao, Yuanhu; Lin, Yongbiao; Liang, Chenfei; Dai, Jun; Liu, Yan; Fan, Pingping; Zhang, Weixin; Fu, Shenglei
Abstract: To illustrate the interplay between top-down and bottom-up forces on the soil microbial community and activity, we conducted a 3-year field experiment investigating the interactions of the dominant, exotic earthworm Pontoscolex corethrurus and the native plant Evodia lepta in subtropical soil. We found that both earthworms and plants were able to regulate soil carbon (C) and phosphorous (P) dynamics by affecting the soil fungi-to-bacteria ratio, as well as the labile C and available P content. The increase in soil respiration in plots with only earthworms was mainly due to the increased proportion of soil bacteria that had a fast turnover and low assimilation efficiency. The increase in soil respiration in plots with only plants was possibly due to an increase in the metabolic quotient of soil microorganisms under the stress of soil available P. The significant decrease of soil available P and increase in soil phosphatase activity indicated an intensified demand for soil available P when plants were present; accordingly, earthworms' effect on soil available P was only significant in plots with plants. Overall, when plants were present, the soil fungi-to-bacteria ratio (F/B) and C dynamics changed in a similar way regardless of the reduction of the earthworm populations. The earthworms' effects on soil P processes were enhanced by the presence of plants. These indicated that plants were one of the key regulators of the effects of earthworms on the soil microbial community and its activity in this subtropical ecosystem. Highlights: Earthworm and plant effects on C and P dynamics were examined in field. Earthworm increased soil respiration through decreasing fungi to bacteria ratio. Plant increased soil respiration through increasing microbial metabolic quotient. Plant regulated soil microbes through exacerbating soil P deficiency. Plant modified the effects of earthworm on soil microbial community and activity.